A Comparative Study of Carbonate Determination in Human Teeth Using Raman Spectroscopy - Spizzirri, P.G.; Cochrane, N.J.; Prawer, S.; Reynolds, E.C. (Caries research, 2012)
Carbonate determination in dental apatites such as dentine and enamel is important for studying the dynamics of dental caries and developmental defects of these tissues. Traditionally, these determinations have been performed by acidic digestion with the subsequent measurement of released carbon dioxide gas. As an alternative, Raman spectroscopy has been used for the determination of carbonate in synthetic carbonated apatites with at least four analytical methods published thus far. However, these methods have not been applied to biological apatites. The aim of this comparative study was to test the suitability of these four methods for the determination of B-type carbonate in human enamel and dentine. A method for determining the A-type carbonate content of enamel using the Raman technique is also presented. Raman spectra were obtained from 10 human enamel and dentine samples and analysed with each of the four methods using either a single or multiple ν 1 (PO 4 3– ) band spectral fitting model. Each of the methods resulted in a different determination for the carbonate content when using the same measurement data. The method that used the full-width-at-half-maximum of the ν 1 (PO 4 3– ) band to determine the B-type carbonate concentration was found to be in best agreement with (i) the results (using the acid digestion method) of teeth collected from the same sample population and (ii) previously reported values for both enamel and dentine. The use of a multiple-band spectral fitting model produced the highest determination precision (particularly in the case of dentine).